Care management services at safety-net clinics in the United States - Joo, Joseph H.; Morenz, Anna M.; Dang, Michael D.; Cardin, Jennifer R.; Liao, Joshua M. (Frontiers in Health Services, 2025)
Federally qualified health centers and rural health centers are key parts of the United States ambulatory safety-net care system. Medicare has sought to encourage care coordination at these safety-net clinics by reimbursing clinicians directly for delivering care management services. In this paper, we described long-term trends in utilization of care management services for Medicare patients at federally qualified health centers and rural health centers vs. non-federally qualified health centers and non-rural health centers. General care management service utilization increased by 207% with 2,251 services submitted in 2023. Denial rates for general care management services increased over time, with 42% of submitted services being denied in 2018, compared to 64% of submitted services being denied in 2023. Compared to general care management services, transitional care management services were delivered far less frequently at federally qualified health centers and rural health centers, with a total of 237 services submitted across the entire six-year study period, and zero services submitted in several study years. Among these services, 188 (79%) were reimbursed with a corresponding cost of $31,551. Despite their greater salience and need for care coordination at safety-net clinics in the United States, there was little utilization of care management services delivered to Medicare patients and reimbursed through the physician fee schedule. The low uptake may reflect a preference for care management services administered outside of Medicare.